Access to Functionalized α-Trifluoromethyl-α-aminophosphonates via Intermolecular Ene–Yne Metathesis - Krylov, Ivan M.; Mailyan, Artur K.; Zotova, Maria A.; Bruneau, Christian; Dixneuf, Pierre H.; Osipov, Sergey N. (Synlett, 2014)
An efficient approach to a new family of highly functionalized P analogues of α-trifluoromethyl-substituted phenylalanine and its homologues using ruthenium-catalyzed intermolecular ene–yne metathesis as a key step of the reaction sequence has been developed. The method includes cross metathesis of α-alkynyl-α-trifluoromethyl-α-aminophosphonates with alkenes under catalysis by second-generation Grubbs carbene complex to afford the corresponding aminophosphonates with 1,3-diene backbone followed by one-pot Diels–Alder reaction–aromatization step.
Keywords: alkynes; diynes; cross-metathesis; aminophosphonates; catalysis